A case of adenoma of the nipple with breast cancer - Asagoe, T; Hanatani, Y; Horie, F; Nemoto, A; Kidooka, K; Shikata, J; Imamura, T (Nihon Geka Gakkai zasshi, 1991)
Adenoma of the nipple is an uncommon lesion which can be mistaken clinically for Paget's disease and pathologically be misinterpreted as an adenocarcinoma. We recently experienced a case of very rare adenoma of the left nipple with left breast cancer. The patient was a 42-year-old, married woman with a firm, partially erosive lump measuring 12 X 12mm in her left nipple and with a left breast lump. Biopsy revealed the breast lump invasive ductal carcinoma and lump of the nipple was adenoma. Modified radical mastectomy was carried out. It is important to bear this rare lesion in mind and perform a thorough examination before making a diagnosis of a lump in the nipple.